Tracking bowfin with acoustic telemetry: Insight into the ecology of a living fossil. Issue 1 (17th February 2017) - Midwood, Jonathan D.; Gutowsky, Lee F.G.; Hlevca, Bogdan; Portiss, Rick; Wells, Mathew G.; Doka, Susan E.; Cooke, Steven J.
Abstract: Little is known about the spatial ecology and behaviour of bowfin ( Amia calva ), despite the fact that it is an important freshwater carnivore, the last living member of the Amiiformes and effectively a living fossil. In the summer of 2013, acoustic telemetry transmitters were surgically implanted in ten bowfin captured in Toronto Harbour on Lake Ontario. Using a stationary acoustic telemetry array that covered most of the 18‐km 2 harbour, the residency and movement patterns of bowfin were tracked from their release until November 2014. Detected bowfin ranged in size from 562 to 725 mm total length and included six males and three females (one female was not detected). Bowfin showed high site fidelity with most fish detections concentrated in embayments and within the Toronto Islands, areas characterised by relatively high stable water temperatures and submerged vegetative cover. Statistical modelling revealed that bowfin residency was significantly affected by season, body size, site‐specific estimates of vegetative cover and an interaction between body size and season. Bowfin residency increased with vegetative cover and was highest for large fish during the winter and fall months. Despite the overall high site fidelity exhibited by individuals, several bowfin were mobile over the spring and summer months and moved 5.2–12.9 km among telemetry receivers in the inner and outer harbours. The results of this study provide insight into the seasonal habitat preference, home range size and activity level of this unique fish.